Impact of Marketing Research on Business Management in Nigeria - N. Dike, Onwubiko (British Journal of Marketing Studies, 2015)
The study assessed the extent of the effects of marketing research on the practice of business management in Nigerian organizations. Survey method was used. The target population was 15,600 registered members of the National Institute of Marketing of Nigeria (NIMN), comprising academic marketers, AM (2200), marketing practitioners, MP (9350) and marketing students MS (4050).Stratified, simple random, convenience and judgmental sampling procedures were adopted. The sample size of 390 was determined using Yamane (1967) formula. Applying Bowley’s proportional allocation formula, the sample size for each category of the respondents was estimated; AM (55), MP (234) and MS (101).One hypothesis and a research question guided the study. Primary and secondary sources were accessed for data. In-depth interviews were held with marketing practitioners and students, academic marketers, coordinators of marketing research firms and secretary of Nigerian Marketing Research Association (NIMRA). The questionnaire adopted the five point Likert scale format, viz, strong agree (5points), agree (4points), undecided (3points), disagree (2points) and strongly disagree (1point). The opinions of marketing experts validated the research instrument. Pilot study was conducted. The reliability coefficient of the research instrument, 0.973 was estimated, using Cronbach’s Alpha technique. With one-way ANOVA and Minitab software techniques, the hypothesis of the study was formulated and tested at 0.05 level of significance and 15degrees of freedom. The study revealed the extent of the effects of marketing research at 18.08 percent had non-significant positive impact on business management practice in Nigerian organizations. Recommendations were made.